Targeting the NLRP3 inflammasome in chronic inflammatory diseases: current perspectives - Ozaki E (Dove Medical Press, 2015)
Ema Ozaki,1 Matthew Campbell,1 Sarah L Doyle2,3 1Department of Genetics, 2Department of Clinical Medicine, School of Medicine, Trinity College Dublin, 3National Children's Research Centre, Our Lady's Children's Hospital Crumlin, Dublin, Ireland Abstract: The inflammasome is a molecular platform formed by activation of an innate immune pattern recognition receptor seed, such as NLRP3. Once activated, NLRP3 recruits the adapter ASC (apoptosis-related speck-like protein containing a caspase recruitment domain), which in turn recruits procaspase-1. Procaspase-1 autocatalyzes its cleavage and activation, resulting in maturation of the precursor forms of interleukin (IL)-1β and IL-18 into active proinflammatory cytokines and initiation of pyroptotic cell death. The NLRP3 inflammasome has been implicated in the pathogenesis of a wide variety of diseases, including genetically inherited autoinflammatory conditions as well as chronic diseases in which NLRP3 is abnormally activated. The NLRP3 inflammasome has been linked to diseases such as Alzheimer's disease, atherosclerosis, metabolic syndrome, and age-related macular degeneration. In this review, we describe the NLRP3 inflammasome complex and its activation in disease, and detail the current therapies that modulate either the NLRP3 inflammasome complex itself or the two cytokines it is responsible for activating, ie, IL-1β and IL-18. Keywords: NLRP3, interleukin-1, interleukin-18, caspase-1, therapeutics, inflammasome